Stability-and-peace accelerator: concept note - Dahl, Hauke; Jacobs-Mata, Inga; Hulbert, S.; Shehata, J. (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2023)
For the 1.5 billion people living in Fragile and Conflict Affected Settings (FCAs), livelihood challenges and rising food, fertilizer, and input prices are compounded by climate change, unsustainable resource consumption, poor governance, and weak social cohesion. Economic disruptions, such as those caused by COVID-19 and the war in Ukraine, are sparking the risk of food and nutrition crises and poverty and conflict traps. Global hunger, remained relatively unchanged from 2021 to 2022 but is still far above pre-COVID-19-pandemic levels, affecting around 9.2 percent of the world population in 2022 compared with 7.9 percent in 2019. It is estimated that between 691 and 783 million people in the world faced hunger in 2022. Considering the midrange (about 735 million), 122 million more people faced hunger in 2022 than in 2019, before the global pandemic. The International Water Management Institute (IWMI) is an international, research-for-development organization, with offices in 15 countries and a global network of scientists operating in more than 55 countries. For over three decades, our research results have led to changes in water management that have contributed to social and economic development. IWMI’s vision is a water-secure world. IWMI targets water and land management challenges faced by poor communities in developing countries, and through this contributes towards the achievement of the Sustainable Development Goals (SDGs) of reducing poverty and hunger and maintaining a sustainable environment. Based on evidence and knowledge drawn from our science, innovative technologies and testing of business models, IWMI works with governments, policymakers, farmers, civil society, water managers, development partners and businesses to solve water problems and scale up solutions. Through partnerships, IWMI combines research on the sustainable use of water and land resources, knowledge services and products with capacity strengthening, dialogue and policy analysis to support implementation of water management solutions for agriculture, ecosystems, climate change and inclusive economic growth. IWMI’s value proposition is unique. It rests on a track record of more than 30 years of rigorous, solutions-oriented water management research, built on long term partnerships at local, country and regional levels, and a sustained field presence across Africa and Asia. IWMI brings a robust and growing track record in implementing evidence-based agribusiness accelerator programs targeted at scaling agrifood system innovations in Africa. IWMI has pioneered and expanded methods around science-driven business acceleration and scaling in multilateral projects as well as the OneCG portfolio (AICCRA, Ukama Ustawi, WE4F) and is adapting the end-to-end methodology to scale CGIAR research innovation, tools and knowledge through private sector innovators in a humanitarian, development and peace context. IWMI is also a Research Center of CGIAR, the world’s largest agricultural research partnership. The CGIAR unites leading agricultural research organizations and possesses a vast network of expertise, resources, research findings and capacity that will be leveraged by the UN World Food Program (WFP) Innovation Accelerator. By collaborating with CGIAR, the WFP Innovation Accelerator can tap into cutting-edge research, data-driven solutions, and further best practices in food systems innovation, food security, sustainable resource management and climate security. This collaboration enables a refined comprehension of the challenges faced in fragile settings, allowing for context-specific interventions that can effectively address issues like food insecurity, land degradation, and water scarcity. By accessing the specialized knowledge within the CGIAR’s Fragility Conflict and Migration (FCM) initiative and additional CGIAR actors, the partnership can ensure the likelihood of success for scaling scientifically validated, climate-smart solutions in the sector, as well as to provide the science-based evidence for inclusive sustainability impact. Given the compounding challenges, the purpose of this program is to identify and enable the scaling of high-impact, high potential innovations which promote the resilience of Food, Land and Water Systems (FLWS) in Fragile and Conflict Affected Settings (FCAs) in migrant and host communities — thus enabling food and nutrition security, climate resilience, social cohesion, and sustainability in emergency and humanitarian settings. In order to achieve this purpose, the program will source high potential innovations, award grants to said innovations, promote capacity building of innovations with a local footprint, and harness the immense technical expertise of CGIAR scientists to support the innovations.